Rationale and Protocol for a Pilot Randomized Controlled Trial of a Cognitive Prescription Intervention for Reducing Dementia Risk Factors Among African Americans - Fazeli PL; Hopkins C; Vance DE; Wadley V; Li P; Turan B; Bowen PG; Clay OJ (Dove Medical Press, 2022)
Pariya L Fazeli,1 Cierra Hopkins,1 David E Vance,1 Virginia Wadley,2 Peng Li,1 Bulent Turan,3 Pamela G Bowen,1 Olivio J Clay4 1School of Nursing, University of Alabama at Birmingham, Birmingham, AL, USA; 2School of Medicine, University of Alabama at Birmingham, Birmingham, AL, USA; 3College of Social Sciences and Humanities, Koc University, Istanbul, Turkey; 4Department of Psychology, University of Alabama at Birmingham, Birmingham, AL, USACorrespondence: Pariya L FazeliDepartment of Family, Community, and Health Systems, UAB School of Nursing, NB 470C, 1720 2nd Avenue South, Birmingham, AL, 35294-1210, USATel +1 205 996 0330Email plfazeli@uab.eduBackground and Purpose: African Americans (AAs) are twice as likely to develop dementia than Whites, which may be driven by poorer dementia knowledge and lifestyle factors. This article provides the rationale and protocol for a pilot clinical trial examining a tailored multidomain lifestyle modification intervention in middle-aged and older AAs. This study will explore the feasibility and efficacy of individualized cognitive prescriptions (CogRx) which target five domains: physical activity, cognitive activity, diet, sleep, and social activity. Theoretical underpinnings include Social Cognitive Theory and the Health Belief Model, which suggest that tailored risk factor information, goal-setting, and outcome expectations along with addressing self-efficacy and barriers will promote behavior change.Study Design: This study plans to enroll 150 community-dwelling AA participants aged 45- 65 without significant cognitive impairment. After baseline assessment including data-driven assessment of deficiencies in each of the five CogRx domains, participants are randomized with equal allocation to either: psychoeducation + CogRx, psychoeducation only, or no-contact control. The psychoeducation and CogRx groups receive general psychoeducation on dementia prevalence, prognosis, and risk factors, while the CogRx group also receives information on their risk factor profile and develops a tailored three-month intervention plan, consisting of simple evidence-based strategies to implement. The CogRx condition receives text-messaging reminders and adherence queries and provides feedback on this program.Conclusion: This study tests a novel multidomain dementia prevention intervention and has several strengths, including enrolling middle-aged AAs with a focus on prevention, assessing adherence and self-efficacy, tailoring the intervention, and examining dementia knowledge. The goal is to yield new perspectives on person-centered dementia prevention approaches in diverse populations and ultimately impact clinical and public health recommendations for maintaining cognitive health, thereby reducing disparities in dementia. Modifications to study design due to COVID-19 and future directions are discussed.Keywords: lifestyle, health behaviors, health literacy, minorities